Projek Penguatan Profil Pelajar Pancasila (P-5) Pada Kurikulum Merdeka Jenjang SMA - Mursidawati M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Pancasila Student Profile is a lifelong student who has competence, character, and behaves according to Pancasila values. The Pancasila profile has six key dimensions that are interrelated and reinforce each other so that they can develop holistically and simultaneously. These six dimensions show that the profile of Pancasila students does not only focus on cognitive abilities, but also attitudes and behavior in accordance with the identity of the Indonesian nation and citizens of the world. The Pancasila Student Profile is the character and abilities that are built in daily life and are lived in each individual student through the culture of the education unit, intra-curricular learning, the Project to Strengthen Pancasila Profile (P-5), and extracurriculars. The Pancasila Student Profile Strengthening Project provides an opportunity for students to experience knowledge as a process of strengthening character as well as an opportunity to learn from the surrounding environment. In project activities, students have the opportunity to study important themes or issues and can take real action in responding to these issues. This strengthening project can also inspire students to contribute and make an impact on the surrounding environment. In order to be able to solve problems in the real world, students must be prepared with experience (knowledge) and competencies that are in accordance with the needs of the times.